2000
DOI: 10.1023/a:1008375208574
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of interleukin (IL)-10 induced by non-small-cell lung cancer

Abstract: These results suggested that the cytoplasmic IL-10 correlated to clinical prognosis, and that IL-10 expression is a prognostic factor for NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
3
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 16 publications
1
61
3
2
Order By: Relevance
“…These findings are in contrast with a previous report of HATANAKA et al [7], who suggested that IL-10 expression by the tumour is an indicator of poor prognosis in NSCLC patients. In the present study, IL-10 expression was analysed at the protein level whereas the mRNA level was analysed by HATANAKA et al [7].…”
Section: Il-10 and Nonsmall Cell Lung Cancer E Zeni Et Alcontrasting
confidence: 99%
See 3 more Smart Citations
“…These findings are in contrast with a previous report of HATANAKA et al [7], who suggested that IL-10 expression by the tumour is an indicator of poor prognosis in NSCLC patients. In the present study, IL-10 expression was analysed at the protein level whereas the mRNA level was analysed by HATANAKA et al [7].…”
Section: Il-10 and Nonsmall Cell Lung Cancer E Zeni Et Alcontrasting
confidence: 99%
“…These findings are in contrast with a previous report of HATANAKA et al [7], who suggested that IL-10 expression by the tumour is an indicator of poor prognosis in NSCLC patients. In the present study, IL-10 expression was analysed at the protein level whereas the mRNA level was analysed by HATANAKA et al [7]. The difference between the present results and those by HATANAKA et al [7] are probably due to the fact that the mRNA measurements were performed globally on tissues including tumour cells, stromal cells and TAMs.…”
Section: Il-10 and Nonsmall Cell Lung Cancer E Zeni Et Alcontrasting
confidence: 99%
See 2 more Smart Citations
“…2 In fact, we previously reported that TGF-b1 was expressed in gastric cancer tissues and correlated with poor prognosis. 16 With regard to IL-10, recent studies demonstrated that IL-10 was also expressed in some cancers, including lung cancer 17 and melanoma. 9 Moreover, it has been reported that IL-10 expression significantly correlated with poor prognosis in non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%